1997
DOI: 10.1111/j.1749-6632.1997.tb48576.x
|View full text |Cite
|
Sign up to set email alerts
|

A Microcosm Study on Remediation of Explosives‐contaminated Groundwater Using Constructed Wetlandsa

Abstract: Anaerobic degradation of TNT and TNB in gravel systems was rapid and similar to removal rates in parrot feather lagoons. Planted and unplanted anaerobic gravel systems were the only treatments that provided significant reduction of RDX and HMX. Planted systems with parrot feather had no effect on removal rates of explosives in anaerobic gravel systems. Reciprocating wetlands were not effective in biodegrading RDX or HMX, but were very efficient at removing COD. A scaled-up concept for bioremediating contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Sikora et al (1997) found both TNT and TNB were rapidly degraded (Figure 3) under anaerobic substrate conditions; however, the presence of M. braziliense made no apparent difference in removal rates. Substrate bacterial action seemed to play the biggest role in explosives degradation (Sikora et al, 1997). Recommendations for larger-scale testing of these degradation pathways is also made by Sikora et al (1997); however, lists of additional wetland plant species (e.g., the screening list of Best et al [1997]) should also be evaluated.…”
Section: Aerobic Vs Anaerobic Conditionsmentioning
confidence: 84%
See 3 more Smart Citations
“…Sikora et al (1997) found both TNT and TNB were rapidly degraded (Figure 3) under anaerobic substrate conditions; however, the presence of M. braziliense made no apparent difference in removal rates. Substrate bacterial action seemed to play the biggest role in explosives degradation (Sikora et al, 1997). Recommendations for larger-scale testing of these degradation pathways is also made by Sikora et al (1997); however, lists of additional wetland plant species (e.g., the screening list of Best et al [1997]) should also be evaluated.…”
Section: Aerobic Vs Anaerobic Conditionsmentioning
confidence: 84%
“…Microcosm design created anaerobic and aerobic conditions by using added carbon to enhance bacterial uptake of oxygen (causing anaerobic waters) and siphon-driven reciprocating water exchange to produce more aerobic waters (Sikora et al, 1997). Sikora et al (1997) found both TNT and TNB were rapidly degraded (Figure 3) under anaerobic substrate conditions; however, the presence of M. braziliense made no apparent difference in removal rates. Substrate bacterial action seemed to play the biggest role in explosives degradation (Sikora et al, 1997).…”
Section: Aerobic Vs Anaerobic Conditionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, in plant selection for wetland construction, consideration of explosives removal potential and biomass production were considered essential. Sikora et al (1997) reported that the anaerobic degradation of TNT and TNB in anaerobic SSF constructed wetland systems was rapid and similar to removal rates in parrot feather wetlands. Vegetated and unvegetated anaerobic SSF systems were found to be the only systems that provided significant reduction of RDX and HMX.…”
Section: Nitrogenous Compoundsmentioning
confidence: 84%